The Analysis of Indoor Air Pollutants From Finishing Material of New Apartments at Business Bay, Dubai - Jung, Chuloh; Al Qassimi, Nahla; Arar, Mohammad; Awad, Jihad (Frontiers in Built Environment, 2021)
Due to fast economic development, Dubai has built many high-rise apartments in a short period of time. The Dubai Municipality attempts to control indoor air quality with strict regulations, but the detailed provisions are still not comprehensive. The objective of this paper is to conduct on-site measurements for new high-rise apartments before moving on to investigate indoor air pollution and to analyze pollutant emissions by type of finishing material. As a methodology, on-site measurements were conducted fornine different housing units (three lower, three middle, and three higher floors) before moving on to investigate the status of indoor air pollution in new apartments. Based on the on-site measurements data, lab experiments with a small chamber for the same finishing materials from the most polluted housing unit (a lower two bedroom unit) were conducted to measure the emission of pollutants over 30 days. The result shows that the average of CH2O (64.4 μg/m3 for studio, 64.5 μg/m3 for one bedroom, and 83.4 μg/m3 for two bedroom) was lower than the standard (100 μg/m3) in all units, while the average TVOC (520.1 μg/m3 in the studio, 509.5 μg/m3 in one bedroom, and 754.7 μg/m3 in two bedroom) exceeded the standard (500 μg/m3) in most of the units. It was proven that regarding the CH2O, silk wallpaper, initial wallpaper, and wallpaper adhesive had the highest emissions and for the TVOC, tile and tile adhesive had the highest emission. During small chamber experiments, CH2O and TVOC emissions tended to decrease gradually over time, but the emission amount changed significantly in high pollutant emission material especially from day 1–10. Therefore, Dubai municipality should establish the regulation for residents to move into their new apartment after at least 10 days to avoid the high polluted emission from the curing process of the interior finishing material.